2023
DOI: 10.1007/s15010-023-02005-y
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Wisely internationally – helpful recommendations for antimicrobial stewardship!

Abstract: Purpose Antimicrobial resistance poses a major threat to human health globally and antibiotic overuse is a main driver of resistance. Antimicrobial stewardship (AMS) was developed to improve the rationale use of antibiotics. The Choosing Wisely campaign was initiated to ameliorate medical practice through avoidance of unnecessary diagnostic and therapeutic procedures. Our objective was to give an overview on the Choosing Wisely recommendations related to AMS practices from a selection of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Interestingly, three urine cultures were obtained, and all of them were evaluated as normal or contaminated. Our findings indicated that age, gender, triage category, and duration of fever are not associated with the incidence of urinalysis, thus suggesting that urinalysis are performed against the guidelines and latest recommendations on urinary tract infection diagnostics [33][34][35].…”
Section: Discussionmentioning
confidence: 72%
“…Interestingly, three urine cultures were obtained, and all of them were evaluated as normal or contaminated. Our findings indicated that age, gender, triage category, and duration of fever are not associated with the incidence of urinalysis, thus suggesting that urinalysis are performed against the guidelines and latest recommendations on urinary tract infection diagnostics [33][34][35].…”
Section: Discussionmentioning
confidence: 72%
“…Finally, in the case of probiotics, lactobacilli are thought to compete with uropathogens for vaginal epithelial adhesion receptors, leading to a prevention of colonization by uropathogenic organisms [ 21 ]. In addition, the increase in antibiotic resistance [ 22 ] and the role of non-antibiotic oral supplements in reducing UTI symptomatic episodes and the use of antibiotics are increasing the interest among physicians and researchers in the use of medical devices containing phytotherapy and nutraceutical compounds [ 9 , 10 , 11 ]. The current EAU Guidelines for urological infections state that the efficacy of herbal products such as cranberry products or herbal/plant extracts remains unclear, but clinicians can recommend their prescription in combination with antimicrobial therapies for the prevention of UTIs based on their favorable benefit-to-harm ratio [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health Commission of the People's Republic of China launched the National Action Plan based on the evaluation and summary of the work effect in the past few years, initiating the National Action Plan to Curb Antimicrobial Resistance (2022-2025) [12]. Antimicrobial stewardship (AMS) is an important strategy for the decrease of antimicrobial resistance and is widely used in antimicrobial management [13]. Clinical pharmacists are identi ed as key members of the AMS team [14].They participate in the whole process of antimicrobial use and management, and play a more prominent role.…”
Section: The Proportion Of Hospitalization Antibiotics Costmentioning
confidence: 99%